Determinants of brain metabolism changes in mesial temporal lobe epilepsy. (8th April 2016) - Chassoux, Francine; Artiges, Eric; Semah, Franck; Desarnaud, Serge; Laurent, Agathe; Landre, Elisabeth; Gervais, Philippe; Devaux, Bertrand; Helal, Ourkia Badia
Summary: Objective: To determine the main factors influencing metabolic changes in mesial temporal lobe epilepsy (MTLE) due to hippocampal sclerosis (HS). Methods: We prospectively studied 114 patients with MTLE (62 female; 60 left HS; 15‐ to 56‐year‐olds) with 18 F‐fluorodeoxyglucose–positron emission tomography and correlated the results with the side of HS, structural atrophy, electroclinical features, gender, age at onset, epilepsy duration, and seizure frequency. Imaging processing was performed using statistical parametric mapping. Results: Ipsilateral hypometabolism involved temporal (mesial structures, pole, and lateral cortex) and extratemporal areas including the insula, frontal lobe, perisylvian regions, and thalamus, more extensively in right HS (RHS). A relative increase of metabolism (hypermetabolism) was found in the nonepileptic temporal lobe and in posterior areas bilaterally. Voxel‐based morphometry detected unilateral hippocampus atrophy and gray matter concentration decrease in both frontal lobes, more extensively in left HS (LHS). Regardless of the structural alterations, the topography of hypometabolism correlated strongly with the extent of epileptic networks (mesial, anterior‐mesiolateral, widespread mesiolateral, and bitemporal according to the ictal spread), which were larger in RHS. Notably, widespread perisylvian and bitemporal hypometabolism was found only in RHS. Mirror hypermetabolism was grossly proportional to the hypometabolic areas, coinciding partly with the default mode network. Gender‐related effect was significant mainly in the contralateral frontal lobe, in which metabolism was higher in female patients. Epilepsy duration correlated with the contralateral temporal metabolism, positively in LHS and negatively in RHS. Opposite results were found with age at onset. High seizure frequency correlated negatively with the contralateral metabolism in LHS. Significance: Epileptic networks, as assessed by electroclinical correlations, appear to be the main determinant of hypometabolism in MTLE. Compensatory mechanisms reflected by a relative hypermetabolism in the nonepileptic temporal lobe and in extratemporal areas seem more efficient in LHS and in female patients, whereas long duration, late onset of epilepsy, and high seizure frequency may reduce these adaptive changes.